Traditional Chinese Medicine Fufang-Zhenzhu-Tiaozhi capsule prevents renal injury in diabetic minipigs with coronary heart disease - Lixia Song; Ke Wang; Jianying Yin; Yiqi Yang; Bo Li; Dongxing Zhang; Hong Wang; Weixuan Wang; Wenjing Zhan; Caijuan Guo; Zhanhui Gu; Lexun Wang; et al. (BMC, 2022)
Abstract Background Renal injury is one of the common microvascular complications of diabetes, known as diabetic kidney disease (DKD) seriously threatening human health. Previous research has reported that the Chinese Medicine Fufang-Zhenzhu-Tiaozhi (FTZ) capsule protected myocardia from injury in diabetic minipigs with coronary heart disease (DM-CHD). And we found significant renal injury in the minipigs. Therefore, we further investigated whether FTZ prevents renal injury of DM-CHD minipig and H2O2-induced oxidative injury of HK-2 cells. Methods DM-CHD model was established by streptozotocin injection, high fat/high-sucrose/high-cholesterol diet combined with balloon injury in the coronary artery. Blood lipid profile, fasting blood glucose (FBG), and SOD were measured with kits. The levels of blood urea nitrogen (BUN), serum creatinine (Scr), urine trace albumin (UALB), urine creatinine (UCR) (calculate UACR), cystatin (Cys-C), and β-microglobulin (β-MG) were measured by ELISA kits to evaluate renal function. TUNEL assay was performed to observe the apoptosis. qPCR was used to detect the mRNA expression levels of HO-1, NQO1, and SOD in kidney tissue. The protein expressions of Nrf2, HO-1, NQO1, Bax, Bcl-2, and Caspase 3 in the kidney tissue and HK-2 cells were detected by western blot. Meanwhile, HK-2 cells were induced by H2O2 to establish an oxidative stress injury model to verify the protective effect and mechanisms of FTZ. Results In DM-CHD minipigs, blood lipid profile and FBG were elevated significantly, and the renal function was decreased with the increase of BUN, Scr, UACR, Cys-c, and β-MG. A large number of inflammatory and apoptotic cells in the kidney were observed accompanied with lower levels of SOD, Bcl-2, Nrf2, HO-1, and NQO1, but high levels of Bax and Cleaved-caspase 3. FTZ alleviated glucose-lipid metabolic disorders and the pathological morphology of the kidney. The renal function was improved and the apoptotic cells were reduced by FTZ administration. FTZ could also enhance the levels of SOD, Nrf2, HO-1, and NQO1 proteins to promote antioxidant effect, down-regulate the expression of Bax and Caspase3, as well as up-regulate the expression of Bcl-2 to inhibit cell apoptosis in the kidney tissue and HK-2 cells. Conclusions We concluded that FTZ prevents renal injury of DM-CHD through activating anti-oxidative capacity to reduce apoptosis and inhibiting inflammation, which may be a new candidate for DKD treatment. Graphical Abstract